Geometrically modified bovine pericardium membrane promotes the expression of molecules targeted for a faster integration and vascularization process - Morgante, Olga; Della Rocca, Ylenia; Marconi, Guya Diletta; Mazzone, Antonella; Cavalcanti, Marcos F. X. B.; Trubiani, Oriana; Diomede, Francesca; Pizzicannella, Jacopo (Frontiers in Bioengineering and Biotechnology, 2024)
In recent years, advancements in technology and the refinement of engineering techniques have facilitated the development of tissue engineering, placing particular emphasis on the use of 3D-biomaterials with several structural and chemical geometric features. In particular, increasing information on biomaterial geometric surfaces has allowed for a better understanding of tissue regenerative processes. In the present study a comparison between BioRipar®, bovine pericardium membrane, modified with micrometric roundish regular open pores (BioR-Ps) and BioRipar® without pores (BioR-NPs) has been investigated. The expression of adhesion molecules such as: fibronectin, vimentin, focal adhesion kinase (FAK), integrin 1, integrin α5, E-cadherin, and molecules involved in neovascularization processes such as: vascular endothelial growth factor (VEGF) and vascular endothelial growth factor receptor (VEGF-R) were evaluated in an in vitro model containing primary culture of human periodontal ligament stem cells (hPDLSCs) through multiparametric analysis. The results indicated a markedly significant expression of all the abovem entioned molecules in hPDLSCs cultured with BioR-Ps compared to hPDLSCs cultured with BioR-NPs. Scanning electron microscopy analysis indicated a marked interaction between the cells and the substrate, particularly evident in the proximity of open pores in the hPDLSCs cultured on the BioR-P surface compared to hPDLSCs cultured on the BioR-NP surface. Thus, the presence of micrometric open pores on the scaffold stimulates the proliferation potential of cells apart from their adhesion ability on the patch, particularly near the pores. Expression of angiogenic molecules strengthened the performance of the modified BioR-Ps. During synthesis, 3D-biomaterial micrometric open-pores enable better bonding between cells and materials, increasing contact area and promoting cellular molecular signals in biomaterial-guided tissue engineering.